RESPON HAMA LASIODERMA SERRICORNE TERHADAP PEMBERIAN FOSFIN FORMULASI (TABLET DAN BAGS) PADA BIJI PINANG - Hayata Hayata (Universitas Batanghari Jambi, 2014)
During storage, areca seed may be attacked by pest. These pests will eat areca seed by perforating it, then ultimately cause the level of quantity and quality decrease. One variety of the pest that attack areca seed called Lasioderma serricorne. To control the pest on areca seed can be done by Fumigation : The Fumigation which should be done in this case is Phospine (PH3). The purpose the experiment is to find out the response of Lasioderma serricorne that is given Phospine in tablet and bags form on areca seed, Which is done by using Competly Randomized Design (CRD) with on factor of Fumigation, Phospine, consist of seven levels of treatment. The conclution is, there is no difference of giving phospine tablet and bags toward the behavior and mortality of Lasioderma serricorne , and fumigation of areca seed in low dosage, 0.25 grams/0.816 m3 or equivalent of 3 grams/m3 has been very effectif for destroying Lasioderma serricorneKey Word : Pest , Lasioderma serricorne , Phospine